2017
DOI: 10.1016/j.ijproman.2017.02.004
|View full text |Cite
|
Sign up to set email alerts
|

An empirical investigation into different stakeholder groups perception of project success

Abstract: Organizations use projects to manage customized, one-off events across a wide range of functions. Project management is an essential operational tool and process that is utilized to effectively and efficiently manage resources, tasks and activities, and associated timelines. The purpose of this paper is to investigate the possibility that failure is a result of different interpretations of the criteria and factors used for success by multiple stakeholder groups. Currently, there is no recorded theory to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(106 citation statements)
references
References 35 publications
2
96
0
8
Order By: Relevance
“…McLean's assumption, which combined the logic of communication [46] and information influence theories [47], the ISRS model was proposed by adopting the above-mentioned logic and combining it with Parasuraman and Colby's [25] readiness constructs. Subiyakto [39,40] explained that the combination assumption was developed by considering the essential issues of stakeholder readiness in IT/IS projects [12,[16][17][18][48][49][50][51] referring to the input-process-output (IPO) logic of Davis and Yen's [52] information processing theory and the process logic of Kellogg's [53] model development theory. The readiness constructs of the TRI model [25], namely, optimism (OPT), innovativeness (INN), discomfort (DIS), and insecurity (INS), were then placed in the input dimension of the ISRS model.…”
Section: Like Delone Andmentioning
confidence: 99%
See 1 more Smart Citation
“…McLean's assumption, which combined the logic of communication [46] and information influence theories [47], the ISRS model was proposed by adopting the above-mentioned logic and combining it with Parasuraman and Colby's [25] readiness constructs. Subiyakto [39,40] explained that the combination assumption was developed by considering the essential issues of stakeholder readiness in IT/IS projects [12,[16][17][18][48][49][50][51] referring to the input-process-output (IPO) logic of Davis and Yen's [52] information processing theory and the process logic of Kellogg's [53] model development theory. The readiness constructs of the TRI model [25], namely, optimism (OPT), innovativeness (INN), discomfort (DIS), and insecurity (INS), were then placed in the input dimension of the ISRS model.…”
Section: Like Delone Andmentioning
confidence: 99%
“…A statistical report by International Telecommunication Union (ITU) [1] demonstrated that despite the fact that the number of mobile users in developing countries has been increasing significantly since the 2000s, this has not resulted in Internet subscription growth. Beringer, et al [16], Davis [17], and Subiyakto, et al [18] noted that technological implementation performance may also refer to stakeholder perceptions. Many previous studies about information technology (IT) implementation success [19][20][21][22][23][24] reported that the performance of technology implementation demonstrates the efficiency, effectiveness, user satisfaction, and conformity with a development plan.…”
Section: Introductionmentioning
confidence: 99%
“…However, in practice, it is a tool for the management of expectations. It is the result of the initial negotiation of the project (Davis 2017), often carried out between the project manager and the sponsor, or between the salesperson and the client.…”
Section: Project Complexity Is the Property Of A Project Which Makes mentioning
confidence: 99%
“…Davis (2014) estuda as distintas percepções do sucesso de projetos, nas visões de diferentes grupos de stakeholders. No entanto, a autora se limita a três grupos de stakeholders (DAVIS, 2014, p. 11): a cúpula estratégica da empresa, a equipe do projeto e os receptores, entendidos como clientes, consumidores e usuários finais.…”
Section: A Teoria De Stakeholders Em Projetosunclassified